The Attitude of Malaysian East Coast Early Childhood Educators towards English and Their Language Support Practices - Noor Raha, Mohd Radzuan; Wan Jumani, Fauzi; Aisyah Khaleeda, Rosli; Fatimah, Ali (2023)
English proficiency is advantageous for any graduate. In Malaysia, despite English being formally introduced around age 5, proficiency in the language is still lacking in some graduates. English should be introduced to children during their formation years so they can be proficient. However, in many private preschools, English proficiency is not a priority in the hiring criteria of early childhood (EC) educators despite the introduction of the Malaysian English Language Education Roadmap 2015-2025. With EC educators being a primary provider of input in the system, it is essential to investigate their attitudes towards English, particularly on the East Coast of Malaysia, where English usage is not as extensive as on the west coast, and how these attitudes translate into their practices with the children. A questionnaire of 29 questions was distributed to 114 EC educators. Findings reveal that positive attitude leads to EC educators using English with the children. Although knowledge of the language may be limited, the positive attitude spurs them to find alternative ways to expose English to the children. The findings hence provide insight to how we can upgrade the quality of existing English language education provided in preschools, mapping it to the Roadmap 2015-2025 for the reform to succeed.